The effect of student professional responsibilities training in the process of clinical education in nursing students - Fatemeh Keshmiri; Khadijeh Nasiriani (BMC Nursing)
Abstract Background Clarifying the role and professional responsibilities of students, followed by conducting educational programs, is a strategy for developing professional behavior that enhances student performance, ensuring the provision of quality and safe education and care. This study aimed to determine the impact of education on the professional responsibilities of nursing students in the clinical education process. Method This quasi-experimental study was conducted with 80 nursing students. A critical-oriented educational program introducing the professional responsibilities of nursing students in clinical education was implemented for the experimental group. The control group received conventional training. A questionnaire measuring accountability in nursing students was used. The data was analyzed using SPSS software version 20. Result Based on the findings, the average overall accountability score among undergraduate nursing students after the intervention was (152.74 ± 11.99) in the intervention group and (133.57 ± 14.46) in the control group, showing a significant difference between the average scores of the two groups, as determined by an independent t-test. Additionally, the average satisfaction score of undergraduate nursing students regarding their understanding of professional responsibilities was (8.7 ± 1.2) in the intervention group and (5.1 ± 1.3) in the control group, indicating a significant difference. Conclusion Implementing a critical-oriented curriculum that introduces the professional responsibilities of nursing students in clinical education enhances students’ understanding of these responsibilities. It is recommended that this curriculum be implemented before students enter clinical training. Clinical trial number Not applicable.